Tipologi Latihan Pada Bahan Ajar Bahasa Jerman Kelas XI - Syamsurijal Syamsurijal (Universitas Negeri Makassar, 2021)
Abstract. The objectives of this study are (i) to describe exercise typology in books of title “Cool: Spaβ beim Deutschlernen” and “Kontakte Deutsch Extra”; (ii) to describe the suitability of exercise typology in both of the books with Curriculum 2013. This research applied descriptive qualitative method. The data were collected through documentation and direct identification using classification table of typology exercise and describe the suitability of the exercises and the curriculum of 2013. The result of the research shows that: (i) the exercises in “Cool: Spaβ beim Deutschlernen” and “Kontakte Deutsch Extra” have already include the four levels exercises by Neuner, those are on the level A of the book “Cool: Spaβ beim Deutschlernen” there are 41 exercises and 137 exercises in the “Kontakte Deutsch Extra”. On the level B, there are 44 exercises in the book “Cool: Spaβ beim Deutschlernen” and 103 exercises in the “Kontakte Deutsch Extra”. For the level C, there are 22 exercises of the book “Cool: Spaβ beim Deutschlernen” and 48 exercises in the “Kontakte Deutsch Extra”. For the level D, there are 6 exercises in the book “Cool: Spaβ beim Deutschlernen” and 5 exercises in the “Kontakte Deutsch Extra”; (ii) the exercises in “Cool: Spaβ beim Deutschlernen” and “Kontakte Deutsch Extra” are already suitable with the four language skills and scientific approach in curriculum 2013.